Decellularized Persian walnut leaf (Juglans regia) as a potential wound dressing scaffold: an experimental study - Kian, Mehdi; Hashemi, Seyedeh Sara; Derakhshanfar, Amin; Darya, Gholam-Hossein; Shahhossein, Zahra; Saharkhiz, Mohmmad Jamal (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionWound dressings often fall short of providing the multifunctional capabilities required for optimal wound healing, such as promoting cell migration, proliferation, and tissue regeneration. Decellularization of plant tissues has gained attention as a potential source of biomaterials for tissue engineering applications due to their favorable characteristics, including pre-existing vascular networks, interconnected porous structure, efficient water transport and retention, high surface area, and a diverse range of mechanical properties.MethodsThis study investigates the feasibility of using decellularized walnut leaves (DWL) as a novel scaffold for wound dressing in a mice model of excisional wounds. The decellularization and bleaching processes were carried out using various chemical agents. DNA and protein quantification and hematoxylin and eosin staining were performed to reveal the successful removal of cells in DWL. Scanning electron microscopy (SEM) was used to indicate that the normal structure of walnut leaves was preserved after chemical decellularization. Chemical characterization was conducted using Fourier-transform infrared (FTIR) and Raman spectroscopy to show the remaining bioactive molecules and components in the structure of DWL.ResultsComparing tensile strength and surface roughness parameters, surface wettability, swelling, and porosity properties of native and DWL indicated no statistical differences between them. SEM analysis demonstrated that human mesenchymal stem cells excellently attach and proliferate on the DWL. Additionally, the biocompatibility and potential of DWL scaffolds to accelerate wound closure and enhance histopathological scores, collagen deposition, and epithelial thickness were observed in a mice model of excisional wounds.DiscussionIn conclusion, DWL shows promising potential for application as a skin wound dressing due to its biocompatibility, ability to promote cell attachment and proliferation, and efficacy in accelerating wound healing.